Specification for dental casting gold alloys (BSI, 1988)
Dentistry, Dental materials, Dental prosthesis, Gold alloys, Castings, Chemical composition, Grades (quality), Specimen preparation, Classification systems, Hardness, Proof stress, Elongation, Toxicity, Marking, Test specimens